Enhancement of chitosanase production by cell immobilization of Gongronella sp. JG - Zhang,Pingping (2013)
Chitosanase production of Gongronella sp. JG cells immobilized in calcium alginate gel and polyurethane foam was compared with that of the free cells, there was a 60% increase in the enzyme yield (2429 U/L) compared to the highest yield obtained from free cells (1513 U/L). The optimal immobilization parameters (concentrations of sodium alginate, calcium chloride, bead inoculums, bead diameter, etc) for the enhanced production of chitosanase were determined as: sodium alginate 2% (w/v), 0.1 M calcium chloride, inoculum 10 mL beads to 100 mL production media and 2.7 mm bead diameter. Maximum chitosanase production was achieved with initial pH of 5.5 and temperature of 30 ºC. The alginate beads had well stability, retained 85% ability of enzyme production even after 7 cycles of repeated batch fermentation. These results showed the immobilization technique was a feasible and economical method for chitosansase production by Gongronella sp. JG.